Rethinking sports history to include sportswomen in 1900s France - Florys Castan-Vicente; Florys Castan-Vicente (Frontiers in Sports and Active Living, 2023)
In the history of French sport, the practice of physical activities by women is essentially considered non-existent before the 1920s, with the exception of a few aristocratic women. Although this idea persists, it has been challenged by recent research on early sportswomen. These studies raise the question of the scope of sports history, and indeed the very definition of sports itself. These are usually defined in the social sciences as physical activities that are organized, codified and institutionalized, structured by clubs and federations. While at the beginning of the 20th century these clubs and federations were most often closed to women, this does not mean that women were not practicing sports. Physical activities were gaining increasing popularity among women even before this time, and not only among the upper class. There is evidence of women swimming, cycling, racewalking, and even wrestling or boxing in the United States, Canada and Britain, as well as in France. These practices necessarily developed outside institutions, with women taking them up as individual pastimes. As demand grew, some sought to profit from this, and sports promoters organized the first competitions. Journalists then reported on these events in the press, sometimes with amusement, sometimes with disapproval.Yet the first women walkers, runners, cyclists and other athletes are only now beginning to appear in historical studies. This paper seeks to contribute to the rehabilitation of these sportswomen, who include working-class boxers and wrestlers, all of whom have long been subject to a double exclusion—institutional and historical. It presents the history of the first competitions of sportswomen—professional or amateur—in France at the turn of the century, a first foundation stone in writing a new and more inclusive history of sport.